Influence of the seed layer on photoactivity inhibition of mica–titania pigments. Issue 6 (1st May 2016) - Gao, Qiang; Wu, Xiaomei; Fan, Yueming; Du, Chang
Abstract: The influence of the seed layer on the phase composition and photoactivity inhibition of mica–titania pigments was investigated. The prior deposition of MnO2 or SnO2 as a seed layer resulted in a complete rutile TiO2 coating without calcinations, while the prior deposition of ZnO led to a mixture of anatase and rutile. The rutile promoting effect of MnO2 and SnO2 could be ascribed to the small lattice mismatch (＜5%) between the seed layer and the rutile TiO2 . Moreover, the seed layer had a great influence on the photoactivity inhibition of mica–titania pigments. A seed layer of MnO2 inhibited the photoactivity of the pigments, whereas a seed layer of SnO2 or ZnO enhanced the photoactivity of the pigments. The degradation rate constant of mica–MnO2 –TiO2 was approximately 72.7% that of mica–TiO2, while the degradation rate constant of mica–SnO2 –TiO2 was approximately 4.5 times as high as that of mica–TiO2 . The influence of the seed layer on the photoactivity of mica–titania pigments depended on the transfer process of electron–hole pairs between the seed layer and TiO2 .